LEGAL LITERACY VILLAGE (Building Legal Awareness for Citizens' Access to Justice in the village of Bendan Kergon, West Pekalongan District, Pekalongan City) - Triana Sofiani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This study will discuss the phenomenon of low legal awareness in the community of Bendan Kergon Pekalongan Village. The study was conducted by applying the Participation Action Research (PAR) approach with the aim of building legal awareness in order to open access to justice for community members. The results of the assistance provided showed an increase in community participation in realizing legal awareness. This is proven by the initiative of Bendan Village residents to form a Community-Based Legal Aid Post (Posbakummas).